منٹو اور فلسفۂ وجودیت: Manto Aur Falsafa e Wajoodiyat - Rahman , Dr. Tanveer ur (Zoraiz, 2025)
Existentialism, as a philosophical movement, gained great momentum in the 20th century and dominated and influenced almost all disciplines. Almost all literary writers and artists went with this wave, because it gave prime importance to man’s existence. Saadat Hassan Manto dealt with major themes of existentialism in his writings. “Thanda Gosht”, “Toba Taik Singh”, “Darpok”, “Boo”, Kali shalwar”, and “Hatak” etc. are evidence that prove Manto’s Existentialist thoughts like ‘Sartre’, Manto violates traditional trends, exposes alienation, and meaninglessness. Furthermore, he believes in man’s free will and freedom of choice.